2022
DOI: 10.1097/wco.0000000000001048
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in autoimmune encephalitis

Abstract: Purpose of reviewAutoimmune encephalitis (AE) refers to immune-mediated neurological syndromes often characterised by the detection of pathogenic autoantibodies in serum and/or cerebrospinal fluid which target extracellular epitopes of neuroglial antigens. There is increasing evidence these autoantibodies directly modulate function of their antigens in vivo. Early treatment with immunotherapy improves outcomes. Yet, these patients commonly exhibit chronic disability. Importantly, optimal therapeutic strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 141 publications
0
10
0
Order By: Relevance
“… 23 Previous studies have also shown that the prognosis of AE patients receiving immunotherapy is good, and the shorter the time from onset to immunotherapy, the better the prognosis. 34 Delayed immunotherapy will aggravate the irreversible damage caused by disturbance of consciousness, which has a significant effect on the prognosis. Therefore, for patients with anti-NMDAR encephalitis with disturbance of consciousness, immunotherapy should be given as soon as possible on the basis of symptomatic treatment, so as to shorten the time from onset to immunotherapy as far as possible, so as to strengthen the curative effect and improve the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Previous studies have also shown that the prognosis of AE patients receiving immunotherapy is good, and the shorter the time from onset to immunotherapy, the better the prognosis. 34 Delayed immunotherapy will aggravate the irreversible damage caused by disturbance of consciousness, which has a significant effect on the prognosis. Therefore, for patients with anti-NMDAR encephalitis with disturbance of consciousness, immunotherapy should be given as soon as possible on the basis of symptomatic treatment, so as to shorten the time from onset to immunotherapy as far as possible, so as to strengthen the curative effect and improve the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…The dosages of Immunoglobin‐G(IgG) control, S100A6 antibody, and IVIG were all 11 pg/ml, which is almost equal to 20% of the mean concentration of S100A6 serum protein (54.99*0.2 = 11.00) in the 10 AE patients. Human immunoglobulin (IVIG) is an effective first‐line immunotherapy for patients with AE (Trewin et al., 2022). Then, 1*10 5 Toledo cells were placed in the inserts for 2 h to penetrate the BBB endothelial layer.…”
Section: Methodsmentioning
confidence: 99%
“…(1) Abnormal immune regulation. Autoimmune-mediated inflammation 50 or neuroinflammation caused by traumatic brain injury, 51 chronic diseases or infections, 52 and toxic metabolites 53 can alter the brain's health status, leading to neuronal damage, abnormal neurotransmitter release, and impaired cognition. (2) Abnormal endocrine function.…”
Section: Main Pathogenesis Of Cognitive Impairmentmentioning
confidence: 99%